Melatonin Alleviates Pyroptosis of Retinal Neurons Following Acute Intraocular Hypertension - Zhang, Yu; Huang, Yanxia; Guo, Limin; Zhang, Yun; Zhao, Mingxuan; Xue, Fuyao; Tan, Cheng; Huang, Jufang; Chen, Dan (CNS & Neurological Disorders - Drug Targets, 2021)
Background: Glaucoma is a multifactorial optic neuropathy progressively characterized by structural loss of Retinal Ganglion Cells (RGCs) and irreversible loss of vision. High Intraocular Pressure (HIOP) is a high-risk factor for glaucoma. It has been reported that the mechanisms of the loss of RGCs are explored in-depth after acute HIOP injury, such as apoptosis, autophagy, and necrosis. However, pyroptosis, a novel type of pro-inflammatory cell programmed necrosis, is rarely reported after HIOP injury. Research studies also showed that melatonin (MT) possesses substantial anti-inflammatory properties. However, whether melatonin could alleviate retinal neuronal death, especially pyroptosis, by HIOP injury is still unclear. Objective: This study explored pyroptosis of retinal neurons and the effects of melatonin in preventing retinal neurons from pyroptosis after acute HIOP injury. Methods: An acute HIOP model of rats was established by increasing the IOP followed by reperfusion. Western Blot (WB) was adopted to detect molecules related to pyroptosis at the protein level, such as GSDMD, GASMDp32, Caspase-1, and caspase-1 p20, and the products of inflammatory reactions, such as IL -18 and IL-1β. At the same time, immunofluorescence (IF) was used to co-localize caspase-1 with retinal neurons to determine the position of caspase-1 expression. Morphologically, ethidium homodimer III staining, a method commonly used to evaluate cell death, was carried out to stain dead cells. Subsequently, Lactate Dehydrogenase (LDH) cytotoxicity assay kit was used to quantitatively analyze the LDH released after cell disruption. Results: The results suggested that pyroptosis played a vital role in retinal neuronal death, especially in the Ganglion Cell Layer, by acute HIOP injury and peaked at 6h after HIOP injury. Furthermore, it was found that melatonin (MT) might prevent retinal neurons of pyroptosis via NF-Κ B/NLRP3 axis after HIOP injury in rats. Conclusion: Melatonin treatment might be considered a new strategy for protecting retinal neurons against pyroptosis following acute HIOP injury.
Keywords: NF-Κ B